Professionalism in Academia; The Role of University Teachers in Sri Lanka - Navaratne Banda, H.M. (My University, 2008)
Universities in Sri Lanka are facing radical expansion and changes. The increasing numbers of students entering the country's limited universities mandate a higher calibre of professionalism among the academic staff. The country's academics, however, face several problems that hinder professional development. The majority of the teaching load is carried by senior and probationary lecturers, thereby limiting their potention for personal development through research and publications. A dearth of qualifies teachers signifies that only a linited number of students receive quality education. Furthermore, there is an uneven distribution of academic staff within the country's universities. The result is a convergence of students, funding and resources on only a select few universities. While Sri Lanka's free education system can and should be considered a national asset, more needs to be done to ensure that the standards of the country's higher education institutions remain competitive in a global context. A motivated and productive teaching staff will lead to effective learning by the students, which then will lead to a qualified and valuable workforce. This article begins by analysing the role of teachers in Sri Lanka's higher education system. It then considers certain universal, professional standards of university teaching that should be employed to enhance the quality of eucation students receive. Finaly, several recommendations are offered for broad changes to organizational structures and traditional practices that relate to the professional development of academics.